The Effect of Education on Hand Washing Using Water and Soap with The 6-Step Method on Children at Anugrah Indah Palembang Kindergarten - Ardiyanto; Sherly Widianti (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Infectious diseases remain a serious threat to the health of school-age children and young children because they love to play, both at school and at home. A child's health is influenced by daily behaviors, one of which is hand washing. Based on the results of a preliminary study on October 12, the researcher conducted an interview with the head of Anugrah Indah Palembang Kindergarten and obtained data on children who did not know about the causes of disease transmission. The number of children who did not know the causes of disease transmission was 50 children. The objective of this study was to determine the effect of hand washing education using water and soap with the 6-step method on children at Anugrah Indah Kindergarten in Palembang. Method: This study used a pre-experimental design with a one-group pre-post test design. Result: The results of the assessment before the 6-step hand washing demonstration showed that out of 51 respondents, 2 respondents had good knowledge, 8 respondents had sufficient knowledge, and 40 respondents had poor knowledge. Conclusion: There was an increase in knowledge of the 6-step handwashing method after the demonstration, with 36 respondents having good knowledge, 13 respondents having adequate knowledge, and 1 respondent having poor knowledge.